Is Philosophy of Nature Irrelevant? - De Haan, Daniel D. (Proceedings of the American Catholic Philosophical Association, 2019)
I contend that the classical approach of Thomists to internecine Thomist debates about the requirements for initiating the enquiries of natural philosophy and metaphysics generates an epistemological crisis which this classical approach cannot overcome on its own terms. Furthermore, the failure of this classical approach to resolve these intractable debates has all too often distracted and stymied Thomists from contributing to the real enquiries of philosophy of nature. This explains, in part, why the most cogent and influential defenders of a return to Aristotelian ideas concerning nature and their relevance to modern science, has come from analytic philosophers unconcerned with these classical Thomist debates. But Thomism need not render itself irrelevant to the philosophy of nature; or so I argue in this essay. I first present a surview of how a classical interpretation of Aristotle’s division of theoretical sciences generated these debates about the relationship between the subjects of metaphysics and natural philosophy. I then argue neither Wippel’s ingenious efforts to secure the autonomy of metaphysics from natural philosophy nor the arguments for the existence of an immaterial being of the natural philosophy first proponents succeed. Hence, the intractable stalemate between these Thomists. Drawing upon the insights of Alasdair MacIntyre I argue for an alternative approach that overcomes this epistemological crisis and helps to secure the relevance of Thomism to the enquiries of philosophy of nature.